2019
DOI: 10.1021/jacs.9b01855
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Doping Stabilized High-Performance P2–Na0.66Li0.18Fe0.12Mn0.7O2 Cathode for Sodium Ion Batteries

Abstract: While sodium-ion batteries (SIBs) hold great promise for large-scale electric energy storage and low speed electric vehicles, the poor capacity retention of the cathode is one of the bottlenecks in the development of SIBs. Following a strategy of using lithium doping in the transition-metal layer to stabilize the desodiated structure, we have designed and successfully synthesized a novel layered oxide cathode P2–Na0.66Li0.18Fe0.12Mn0.7O2, which demonstrated a high  capacity of 190 mAh g–1 and a remarkably high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
164
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 228 publications
(175 citation statements)
references
References 50 publications
8
164
3
Order By: Relevance
“…One is the edge‐sharing site (Na e ), and the other is face sharing with adjacent oxide layers (Na f ). A preferred occupancy at Na e sites is observed because of lower electrostatic repulsion at this position, which is commonly observed in P2‐type compounds . The specific crystallographic data of P2‐NNMO and P2‐NLNMO are listed in Tables S2 and S3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…One is the edge‐sharing site (Na e ), and the other is face sharing with adjacent oxide layers (Na f ). A preferred occupancy at Na e sites is observed because of lower electrostatic repulsion at this position, which is commonly observed in P2‐type compounds . The specific crystallographic data of P2‐NNMO and P2‐NLNMO are listed in Tables S2 and S3, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…To suppress the over extraction of Na atoms contributing to crystal distortion in Na 1.2 Mn 0.8 O 2 , we substitute 0.2 M Na atoms with Li atoms inspired by literatures . P2‐Li 0.2 Na 1.0 Mn 0.8 O 2 was synthesized through conventional solid‐state reaction among Li 2 CO 3 , Na 2 CO 3 , and MnCO 3 mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Methods such as doping various transitional metal and alkaline metal (AM) have been proposed to restrain the P2‐O2 transition . Chen et al have shown that substituting lithium in the manganese position is a bright approach cause that the clustering between Mn 4+ and the Li + can effectively stabilize the adjacent oxygen ions and therefore restraining the P2‐O2 gliding . Lithium doping was also previously testified to be quite valid on P2‐Na 0.85 Li 0.17 Ni 0.21 Mn 0.64 O 2 , Na x [Li y Ni z Mn 1‐y‐z ]O 2 , P2‐Na 0.80 [Li 0.12 Ni 0.22 Mn 0.66 ]O 2 , and P2‐O3 Na 2/3 Li 0.18 Mn 0.8 Fe 0.2 O 2 cathodes …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the requirement for the discharge rates of sodium‐ion batteries is much higher/faster than charge. Therefore, as well as the previous researches, the rate capabilities are tested by charging at low current and discharging at various currents. Specifically, the cells were charged at a constant current density of 24 mA g −1 and discharged at 12–4800 mA g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%